The long-term prognostic value of E/e’ in patients with ST segment elevation myocardial infarction - Jino Park; Yeo-Jeong Song; Seunghwan Kim; Dong-Kie Kim; Ki-Hun Kim; Sang-Hoon Seol; Doo-Il Kim; Sang-Jin Ha (Indian Heart Journal, 2022)
Objectives: This study aimed to evaluate the long-term prognostic value of E/e’ ratio in patients with ST-segment elevation myocardial infarction (STEMI). Methods: We retrospectively assessed 314 patients who underwent primary coronary interventions between January 2010 and December 2015. The included patients were classified into two groups according to the E/e’ ratios: E/e’<15 (n = 245) and E/e’≥15 (n = 69). We investigated the incidence of major adverse cardiac events (MACEs) from the event to the final follow-up period of at least three years. Results: A total of 55 cases of MACEs occurred during the follow-up. The E/e’≥15 group showed a significantly higher rate of MACEs than the E/e’<15 group (34.8% vs. 12.7%, p < 0.001). Among the MACE, the percentage of cardiac deaths (17.4% vs. 0.4%, p < 0.001) was higher in the E/e’≥15 group than in the E/e’<15 group. In the multivariable model, E/e’≥15 was demonstrated as the strongest prognostic factor for MACEs (hazard ratio [HR], 2.597; 95% confidence interval [CI], 1.294–5.211; p = 0.007) and cardiac death (HR, 27.537; 95% CI, 3.287–230.689; p = 0.002), while left ventricular ejection fraction (LVEF) was not. Neither the discrepancy of systolic nor diastolic function between initial and follow-up echocardiography affected the overall prevalence of MACEs. A disparity was observed between the two groups, with a significant increase in the rate of MACEs in the E/e’≥15 group (log-rank test, p < 0.001). Conclusion: The baseline E/e’≥15 in patients with STEMI after successful reperfusion is the strongest predictor of poor long-term clinical outcomes among those analyzed.